How to Engage in Pseudoscience With Real Data: A Criticism of John Hattie’s Arguments in Visible Learning From the Perspective of a Statistician - Bergeron, Pierre-Jérôme; Rivard, Lysanne (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2017)
This paper is a forum contribution that appeared in issue 51-2 in French. Due to the “positive buzz” it garnered following its publication, the MJE editorial team has made its translation available to our English readers. The original version can be accessed here: http://mje.mcgill.ca/article/view/9394.